(3TQM Ydi BOGH GdHQchjs - (3GdbGRBHGOj, CMeO Hf eMeO Hf ESMGb, (B1163 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj COHfG HGdefGXQI (B... (3gPg cdeGJ Ydi QSGdI aj GdBOGH efShHI eMeO Hf HjQ Ydi GdHQchj bGd GdeUfa QMeg Gddg HYO GdJHQc HGdJSejI BOGA dHYV eG hLH Yjg GdMeO ddg QH GdYGdejf (B...s
(3BNQgG (B:s
... (3efGbVI aj GdLedI eY Cfg dG jMJGL Edi TGgO aj SGFQ GdefGbVGf deG eQ hbS Ydi gPG Edi Gfg jfJgj Edi YLR CMOgeG Cj Edi YLR CNO GdePchQjf ef GdefGXQ hGdSGFd JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\242s
(3EjVGM Gdecfhf (B1\3s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs